The Impact of COVID-19 on the Lives and Jobs of Workers in Vietnam's Industrial Zones - Thi Bich Phuong, Tran; Hai Trang, Vu (VNU Journal of Science: Policy and Management Studies, 2022)
People's thinking and awareness of their habits and lifestyles have changed as a result of the COVID-19 epidemic in order to adapt to the new situation. The pandemic not only threatens people's health, but it also threatens the global economy. Workers in industrial zones risk losing their jobs, being laid off, or having to work from home. When faced with problems such as changing jobs, reducing income, and complying with epidemic prevention measures, they must change their daily living habits. The purpose of this article is to investigate the impact of COVID-19 on the lives and jobs of workers in industrial zones. The article's findings can be used as a reference by managers and social policymakers to make appropriate adjustments and support measures for workers in industrial zones in the face of industrial zone difficulties casued by COVID-19.